Ethnomathematics of Madurese Cultural Characteristics in the Emancipated Curriculum - Sri Indriati Hasanah; Moh Zayyadi; Chairul Fajar Tafrilyanto; Yoga Dwi Windy Kusuma Ningtyas (Journal of Innovation in Educational and Cultural Research, 2024)
The concept of mathematics is inextricably linked to the fabric of everyday life. Indeed, the cultural milieu of a given region can also profoundly influence how mathematical concepts are employed. Ethnomathematics represents a component of the mathematical learning process that integrates mathematical concepts within a given culture. This study aims to ascertain the characterization of ethnomathematics within the Madurese culture as reflected in the emancipated curriculum in Bangkalan Regency. This study employs an ethnographic approach, following a series of stages or cycles. The ethnographic research cycle comprises six stages: the selection of an ethnographic project, the formulation of ethnographic questions, the collection of ethnographic data, the production of ethnographic recordings, and the analysis of ethnographic data. Thematic ethnographic analysis was employed as the data analysis technique in this ethnographic study to provide a comprehensive description of the characteristics of Madurese culture in the emancipated curriculum. The research report's primary focus is a descriptive account of the cultural context. This study's findings indicate that mathematical concepts are embedded within the Madurese culture in Bangkalan Regency and can be leveraged as a learning medium in educational activities and as a representation of real-world mathematical geometry. Consequently, integrating these mathematical concepts within the Madurese culture in Bangkalan Regency can enhance students' comprehension of geometry.